(untitled) (International Journal of Biology and Chemistry, 2023)
For the first time the component composition of essential oil of Rhodiola algida (Ledeb.) Fisch & C.A. Mey. family Crassulaceae, collected in places of natural growth in July 2020 in the Kazakh Altai was studied. The component composition of essential oil of this species was determined by gas chromatography and chromatography-mass spectrometry. The method of chromatography-mass spectrometry detected 100 components, of which 79 substances were identified, accounting for 82-83% of the total essential oil. Antioxidant activity was determined by the FRAP method. R. algida essential oil showed low antioxidant activity compared with butyl hydroxyanisole (BHA) at concentrations of 0.25-1.0 mg/ml, confirming the antioxidant properties of R. algida. Based on the results of cytotoxic activity against Artemia salina L. larvae, it was concluded that R. algida essential oil has good lethal toxicity at all concentrations tested, which proves the cytotoxicity of R. algida. At present, studies of R. algida based on substances from this plant and methods of their analysis are of direct interest for phytopreparation.